Magnesium‐Ion Batteries: High‐Rate and Long Cycle‐Life Alloy‐Type Magnesium‐Ion Battery Anode Enabled Through (De)magnesiation‐Induced Near‐Room‐Temperature Solid–Liquid Phase Transformation (Adv. Energy Mater. 45/2019). Issue 45 (5th December 2019) - Wang, Lin; Welborn, Samuel S.; Kumar, Hemant; Li, Manni; Wang, Zeyu; Shenoy, Vivek B.; Detsi, Eric
Abstract : In article number 1902086, Eric Detsi and co‐workers develop a Mg2 Ga5 alloy‐type anode with an extremely long‐cycle life of 1000 cycles, achieved at a relatively high (dis)charge rate of 3C, taking advantage of near‐room‐temperatures solid‐liquid phase transformations between Ga(liquid) and Mg2 Ga5 (solid) . This concept should open the way to the development of practical anodes for next‐generation magnesium‐ion batteries.